Changes in health over time in patients with symptoms allegedly caused by their dental restorative materials - Tillberg A, Berglund A, Ma°rell L, Bergdahl J, Eriksson N, Linde´n G, Stenberg B, (Blackwell Synergy, 2005)
In Sweden, many patients with symptoms allegedly caused by their dental materials have exchanged their restorations, but the effects of the exchange have been insufficiently investigated.